Stage‐specific impact of pelvic lymph node dissection on survival in patients with non‐metastatic bladder cancer treated with radical cystectomy - Abdollah, Firas; Sun, Maxine; Schmitges, Jan; Djahangirian, Orchidee; Tian, Zhe; Jeldres, Claudio; Perrotte, Paul; Shariat, Shahrokh F.; Montorsi, Francesco; Karakiewicz, Pierre I. (BJU international, 2012)
Study Type – Therapy (cohort) Level of Evidence 2b What's known on the subject? and What does the study add? In patients treated with radical cystectomy, pelvic lymph node dissection may have a beneficial effect on cancer control outcomes. We examined the effect of pelvic lymph node dissection on stage‐specific cancer control outcomes. OBJECTIVE • To examine the effect of stage‐specific pelvic lymph node dissection (PLND) on cancer‐specific (CSM) and overall mortality (OM) rates at radical cystectomy (RC) for bladder cancer. METHODS • Overall, 11 183 patients were treated with RC within the Surveillance, Epidemiology, and End Results database. • Univariable and multivariable Cox regression analyses tested the effect of PLND on CSM and OM rates, after stratifying according to pathological tumour stage. RESULTS • Overall, PLND was omitted in 25% of patients, and in 50, 35, 27, 16 and 23% of patients with respectively pTa/is, pT1, pT2, pT3 and pT4 disease (P < 0.001). • For the same stages, the 10‐year CSM‐free rates for patients undergoing PLND compared with those with no PLND were, respectively, 80 vs 71.9% (P = 0.02), 81.7 vs 70.0% (P < 0.001), 71.5 vs 56.1% (P = 0.001), 43.7 vs 38.8% (P = 0.006), and 35.1 vs 32.0% (P = 0.1). • In multivariable analyses, PLND omission was associated with a higher CSM in patients with pTa/is, pT1 and pT2 disease (all P ≤ 0.01), but failed to achieve independent predictor status in patients with pT3 and pT4 disease (both P ≥ 0.05). • Omitting PLND predisposed to a higher OM across all tumour stages (all P ≤ 0.03). CONCLUSIONS • Our results indicate that PLND was more frequently omitted in patients with organ‐confined disease. • The beneficial effect of PLND on cancer control outcomes was more evident in these patients than in those with pT3 or pT4 disease. • PLND at RC should always be considered, regardless of tumour stage.